Cost of hemodialysis after coverage by national health insurance in Japan: a sharing experience with Indonesian health reform system (Faculty of Medicine Universitas Indonesia, 2014)
About 50 years ago, Japan established a health insurance system covering the entire population, and started a period of rapid economic growth, similar to what is happening now in Indonesia. Although improvements in health conditions definitely contributed to the development of modern Japan, the costs of medical care became a serious burden on the economy. In this short report, we review the concept of medical care expenditure in Japan, focusing especially on end-stage renal disease, to provide suggestions to medical reform in Indonesia.